HUBUNGAN DUKUNGAN KELUARGA DALAMMENGONTROL GULA DARAH DENGAN KEPATUHANMINUM OBAT PADA PENDERITA DIABETES MELITUS DIWILAYAH KERJA PUSKESMAS KOTA KALER - Ai Pupu Purnama Wilayanti, - (2023)
Diabetes melitus is a disease of the chronic metabolic system associated with abnormal insulin production characterized by high blood sugar levels. One of the therapies for Diabetes melitus sufferers is adherence to taking medication and in the process of carrying it out family support is a supporting factor for adherence to taking medication because the success of therapy depends on the treatment. The purpose of this study was to determine the relationship between family support in controlling blood sugar and adherence to taking medication in patients with Diabetes melitus. Methods: The research design in this research is a quantitative descriptive correlation survey. The number of samples in this study were 51 respondents using convenience sampling and the research location was carried out in the working area of the Kotakaler Health Center. Data was collected using a questionnaire and data analysis was carried out in this study using a frequency distribution and then analyzing the Chi-Square test. Results: The results showed that family support was in the good category (51%), the level of adherence in taking diabetes mellitus medication was (49%) in the adherent category, and the relationship between family support and adherence to taking medication for diabetes mellitus (ɑ = 0.017). Conclusion: In this study it can be concluded that there is a relationship between family support and the level of medication adherence in people with diabetes mellitus. Keywords: Family Support, Diabetes melitus, Medication Compliance